A study of rigid polyurethane foams: The effect of synthesized polyols and nanoporous graphene. Issue 26 (2nd March 2017) - Hoseinabadi, Morteza; Naderi, Mehdi; Najafi, Mohammad; Motahari, Siamak; Shokri, Mohammad
ABSTRACT: Rigid polyurethane foams (RPUF) with nanoporous graphene (NPG) were synthesized and their properties, including density, mechanical, morphological, and thermal‐resistant properties were studied. In the current work, polyols of the RPUF formulation were synthesized and NPG content was varied from 0.1 to 0.5 wt %. Scanning electron microscopy (SEM) observation was used to observe the dispersion of NPG and cell size in the RPUF nanocomposites. Only 0.25 wt % of NPG improved compressive strength and modulus respectively by 10.7% and 66.5%. The TGA analysis confirmed that an increase in NPG loading slightly increase the degradation temperature of the samples. These results additionally indicated that NPG enhances the mechanical properties of the RPUF nanocomposites more effectively compared to other nanoparticles (clay, silica etc.). The superiority of NPG over other nanoparticles can be attributed to unique two‐dimensional geometrical morphology and a higher specific surface area. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45001. Abstract :